THE USE OF DRILLS ON TEACHING TRANSACTIONAL INTERACTIONAL TALK - Muhammad Fadhol Arofah; Sofian Sofian; Luwandi Suhartono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research was intended to find out how Drills technique effective or not as a technique to teach the speaking skill in transactional-interactional talk. As the purpose of this research was to know the effectiveness of this technique to teach students’ speaking skill, the method used in this research was pre-experimental research in which the researcher concerned with the effectiveness of the technique to teach students’ speaking skill. The findings of this research showed that the use of drills encouraged students to be more active in teaching learning process. The students’ mean score of pre-test was 82.5 and the students’ mean score of post-test was 94. It means the students’ mean score increased 1.15 points. Furthermore, the writer found the t-value (6.68) is higher than the t-table (2.030) with degree of freedom (df = N-1) at the level 5% (0.05). It means the effectiveness of drills technique in teaching speaking is high because it increased the students’ mean score. From the research result can be concluded that the use of drills technique in teaching speaking transactional interactional is effective.Keywords: Drills, Speaking, Transactional-Interactional